COLLOCATIONS WITH THE ADJECTIVE+NOUN FORMULA - Mirzajanova Ra'no Abduraimovna (American Journals, 2023)
This article explores the use of collocations with the adjective+noun formula. Collocations are words that frequently occur together in a language, and the adjective+noun formula is a common pattern for constructing phrases. The aim of this article is to provide an overview of the methods used to identify and analyze collocations with the adjective+noun formula, present the results of previous studies on this topic, discuss the implications of these findings, and provide suggestions for future research.
Keywords: collocations, adjective noun formula, language patterns, phraseology, corpus linguistics